Association Between Red Blood Cell Distribution Width and Thyroid Function - Zhou, Guowei; Ai, Yueqin; Guo, Song; Chen, Quan; Feng, Xiao; Xu, Kun; Wang, Gaoyuan; Ma, Chaoqun (Frontiers in Endocrinology, 2022)
Aim: Red blood cell distribution width (RDW) is an important parameter with broad biological implications. However, the study investigating the association between RDW and thyroid function remains sparse and inconsistent. We aimed to investigate the association between RDW and thyroid function in the US population. Methods: A cross-sectional analysis was performed using the data from the National Health and Nutrition Examination Survey (NHANES) conducted from 2007 to 2010. The thyroid parameters investigated were mainly free triiodothyronine (fT3), free thyroxine (fT4), thyroid-stimulating hormone (TSH), anti-thyroglobulin antibody (TgAb), and anti-thyroperoxidase antibody (TPOAb). In the 6895 adults aged 18 years or older, logistic regression modeling was applied to estimate the association between RDW quartiles and thyroid parameters. Smooth curve fittings and generalized additive models were then performed to address the nonlinear relationship. Results: The association between RDW and TSH followed a J-shaped curve, and a significant positive relationship existed in the 12.5%-17.5% range of RDW [β = 0.350, 95% confidence interval (CI): 0.225 to 0.474], which was prominent in females. We further demonstrated a negative association (β = -0.018, 95%CI: -0.030 to -0.005) between RDW and fT3. Moreover, elevated RDW was more likely to be subclinical hypothyroidism. However, there was no obvious association between RDW and fT4. Conclusion: This study confirmed a significant association between RDW and TSH, and future studies are needed to elucidate the underlying mechanisms of the peculiar RDW-fT3 relationship. RDW may be a significant clinical marker of subclinical hypothyroidism.